Ensaio clínico randomizado duplo-cego comparando a eficácia, longevidade e tolerância de duas concentrações de peróxido de carbamida utilizadas no clareamento vital caseiro - Meireles, Sônia Saeger (2008)
The aim of this double-blind randomized clinical trial was to verify the efficacy, longevity and tolerability of two carbamide peroxide concentrations used in at home vital bleaching. Ninety-two volunteers with shade mean C1 or darker for the six maxillary anterior teeth were randomized into two groups (n= 46) according to bleaching carbamide peroxide concentration: 10% (CP10) or 16% (CP16). Participants were instructed to use the whitening agent in a tray for two hours/day during three weeks. Shade evaluations were done with a value-oriented shade guide and a digital spectrophotometer at baseline and, at one week, 6 and 12 months after bleaching treatment. Tooth sensitivity was measured daily using a scale ranging from 0 (no sensitivity) to 4 (severe sensitivity). At 6 and 12-month follow-up periods, a questionnaire was applied including questions related to alimentary habits and oral hygiene aiming to verify if these factors could influence the durability of the bleaching treatment. One-week post-bleaching, both carbamide peroxide concentrations resulted in teeth significantly lighter than at baseline (p< 0.001) and, there were not significant differences between groups (p> 0.1). The group treated with CP16 related more tooth sensitivity during the first (p= 0.02) and third (p= 0.01) weeks of treatment than the CP10 group. However, no major difference was observed (p= 0.09) when the degree of tooth sensitivity between groups was compared. After 12-month follow-up, both concentrations resulted in tooth significantly lighter than baseline for all color parameters (p< 0.01) and tooth shade median (p< 0.001), and there was a tooth shade median relapse for CP16 when compared to 1-week post-bleaching (p< 0.04). At 6 and 12-month recalls, subjects from CP10 and CP16 reported a high consumption of beverage and food stains, which was not different between groups (p= 0.5). Both carbamide peroxide concentrations tested were well-tolerated and, although the shade relapse had been observed for the CP16 group, the whitening effect remained satisfactory after 12-month follow-up